Implementasi Sistem Manajemen Mutu ISO 9001:2000 di Perpustakaan - Aziz, Syafrudin (Pustakaloka, 2012)
This writting wil be discusion about quality standard management implemntation system of ISO 9001:2000 in library institution. The word ISO is taken from Greek which means same and 9001 is standard related to quality management. The implementation of ISO in library is a sustainable process which need all supports. To apply it, needs four steps: 1) planning 2) document compiling and validating 3) certification. The advantages of implementation of ISO are first, promoting the trust and library userÂ satisficatory by means of organized systematic quality insurance. Second, promoting, image and competitive strength in the global market. Third, Promoting the awareness of library quality. Fourth, trigerring and creating positive changes in terms of quality culture at the institution of library